Knowledge, Attitude and Quality of Life among Type 2 Diabetic Patients in Palestine (Medico Legal Update, 2021)
The purpose of this study is to investigate the association between knowledge and attitude on quality of lifeamong diabetic patients type 2 in Palestine.Method: A cross-sectional quantitative descriptive study that contains a sample of 120 diabetic patientswere selected from Nablus hospitals and outpatient clinics to assess the level of knowledge and attitudestoward self-care and health-related quality of life.Results: The mean score of Michigan Diabetic Knowledge Test was 8.04±2.48 and this consider a moderatelevel. Of 120 diabetic patients, 27.5% had poor knowledge; 65.5% had moderate knowledge, and only 6.6% had good knowledge. The mean for attitude score of all respondents was 125.4±10.57 and this considera positive attitude. There was a significant positive association between knowledge, attitude with HRQol(P=0.00). The mean for HRQoL score was 0.72 and it represented a moderate level of quality of life.Conclusion: Level of knowledge scores and HRQol were moderate and attitude toward the disease waspositive in type 2 diabetic patients in Palestine, and there was a strong association between knowledge,attitude on HRQoL.